1995
DOI: 10.1021/ma00118a045
|View full text |Cite
|
Sign up to set email alerts
|

Statics and Dynamics of .omega.-Functionalized Block Copolymers of Styrene and Isoprene

Abstract: The statics and dynamics of cw-functionalized diblock copolymers of styrene and isoprene have been studied with small-angle X-ray scattering (SAXS) and with rheology and dielectric spectroscopy. The asymmetric diblock copolymers (wps «= 30%) had a dimethylamino or zwitterion group at either end of the chain, and the molecular weights were in the range (0.62-2.44) x 104. Depending on the temperature, the SAXS results revealed two separate levels of microphase separation, one between the polystyrene (PS) and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 9 publications
6
34
0
Order By: Relevance
“…This situation in the symmetric copolymers is in sharp contrast to the asymmetric case studied earlier. [12,13] In the asymmetric copolymers an additional broad reflection was found corresponding to correlations between ionic aggregates with a spacing smaller than the periodicity of the (hexagonal) lattice. In the present case, an aggregation peak is absent implying weak correlations between aggregates and/or much smaller distances.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This situation in the symmetric copolymers is in sharp contrast to the asymmetric case studied earlier. [12,13] In the asymmetric copolymers an additional broad reflection was found corresponding to correlations between ionic aggregates with a spacing smaller than the periodicity of the (hexagonal) lattice. In the present case, an aggregation peak is absent implying weak correlations between aggregates and/or much smaller distances.…”
Section: Resultsmentioning
confidence: 98%
“…The conversion of the amine block copolymers to the sulfo-zwitterion derivatives was achieved by reaction with cyclopropanesultone as described in detail elsewhere. [12] Characterization The copolymers were extensively characterized by a variety of methods. Molecular weight distributions and homogeneity of final, and intermediate, products were determined by size exclusion chromatography (SEC).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was found that the terminal tertiary amine of polymer A forms ionic bond with either of the terminal sulfonic acid or carboxylic acid of polymer B to afford the AB block co-polymers [36,37]. The morphologies of the block co-polymers thus obtained resemble closely those found with the corresponding covalently bonded block co-polymers [38][39][40][41]. Very recently, Hadjichristidis and co-workers have reported the synthesis of four-arm asym- Chain-end-functionalities were more than 95% in all samples.…”
Section: Block Co-polymers and Asymmetric Star-branched Polymers Via mentioning
confidence: 72%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Additionally, a number of fundamental studies aimed at the elucidation of physical phenomena like block copolymer phase behavior, polymer adsorption, adsorbed polymer brush structure, and colloid stabilization and so on were made possible through the use of end-functionalized polymers. [26][27][28][29][30][31][32][33][34][35][36] Nature, number, and position of the end groups have been varied in different ways as well as the nature of the polymeric chain. Particular attention has been paid to the case of polymers bearing zwitterionic sulfobetaine groups.…”
Section: Introductionmentioning
confidence: 99%